HIV‐1 drug resistance among individuals who seroconverted in the ASPIRE dapivirine ring trial. Issue 11 (11th November 2021) - Parikh, Urvi M.; Penrose, Kerri J.; Heaps, Amy L.; Halvas, Elias K.; Goetz, B. Jay; Gordon, Kelley C.; Hardesty, Russell; Sethi, Rahil; Schwarzmann, William; Szydlo, Daniel W.; Husnik, Marla J.; Chandran, Uma; et al.
Abstract: Introduction: A potential concern with the use of dapivirine (DPV) for HIV prevention is the selection of a drug‐resistant virus that could spread and reduce the effectiveness of non‐nucleoside reverse transcriptase (NNRTI)‐based first‐line antiretroviral therapy. We evaluated HIV‐1 seroconversions in MTN‐020/ASPIRE for selection of drug resistance and evaluated the genetic basis for observed reductions in susceptibility to DPV. Methods: MTN‐020/ASPIRE was a placebo‐controlled, Phase III safety and effectiveness study of DPV ring for HIV‐1 prevention conducted at 15 sites in South Africa, Zimbabwe, Malawi and Uganda between 2012 and 2015. Plasma from individuals who seroconverted in ASPIRE was analysed for HIV‐1 drug resistance using both population Sanger sequencing and next‐generation sequencing (NGS) with unique molecular identifiers to report mutations at ≥1% frequency. DPV susceptibility of plasma‐derived recombinant HIV‐1 containing bulk‐cloned full‐length reverse transcriptase sequences from MTN‐020/ASPIRE seroconversions was determined in TZM‐bl cells. Statistical significance was calculated using the Fisher's exact test. Results: Plasma from all 168 HIV seroconversions were successfully tested by Sanger sequencing; 57 of 71 DPV arm and 82 of 97 placebo (PLB) arm participants had NGS results at 1% sensitivity. Overall, 18/168 (11%) had NNRTI mutations including K101E, K103N/S, V106M, V108I, E138A/G, V179D/I/T and H221Y. Five samples from both arms had low‐frequency NNRTI mutations that were not detected by Sanger sequencing. The frequency of NNRTI mutations from the DPV arm (11%) was not different from the PLB arm (10%; p = 0.80). The E138A mutation was detected in both the DPV (3 of 71 [4.2%]) and PLB arm (5 of 97 [5.2%]) and conferred modest reductions in DPV susceptibility in some reverse transcriptase backgrounds but not others. Conclusions: HIV‐1 drug resistance including NNRTI resistance did not differ between the DPV and placebo arms of the MTN‐020/ASPIRE study, indicating that drug resistance was not preferentially acquired or selected by the DPV ring and that the preventive benefit of DPV ring outweighs resistance risk.